Oral Subchronic Toxicity Test of Yellow Root Ethanol Extract (Arcangelisia flava Merr.) In Rats (Mus musculus): Uji toksisitas subkronik oral ekstrak etanol akar kuning (Arcangelisia flava Merr.) pada Mencit (Mus musculus) - Rakhmadani Gadis Aprilianti; Tsaniaturrizqiah Permataningtyas; Fendi Yoga Wardana (Universitas Tadulako, 2022)
Background: Yellow root (Arcangelisia flava Merr.) is a native Indonesian plant that contains alkaloids, phenolics, flavonoids, saponins, tannins and berberine. This plant is proven to have antimicrobial, antioxidant, antihyperlipidemic, and anticancer activity. However, the effect on body weight, clinical symptoms and toxic symptoms has not been studied yet. Objectives: Accordingly, the objective of this research was to determine the effect of Arcangelisia flava Merr. extract with the multilevel maceration method on parameters of body weight, clinical symptoms and toxic symptoms in male rats. Material and Methods: A total of 16 male rats aged 6-8 weeks weighing 20-40 grams were divided into 4 groups. The control group was only given 1% sodium-carboxymethyl cellulose (CMC-Na), while the treatment group was given Arcangelisia flava Merr. extract at doses of 800, 900, and 1000 mg/kgBW orally for 28 days. At week 1 to week 4, body weight, clinical symptoms and toxic symptoms were observed for male rats. Result: Observations of toxic symptoms and symptoms showed that there were several symptoms that appeared in male rats and changes in body weight there were no significant differences from t0 to t1, t0 to t2, t0 to t3, and t0 to t4 for each treatment (p>0,05). Conclusions: The administration of Arcangelisia flava Merr. extract at doses of 800, 900, and 1000mg/kgBW for 28 days did not affect weight gain or loss, but these extracts did have an effect on symptoms in test animals such as straight fur and strange behavior.